Mendeley Software Training in Facilitating Reference Management in Thesis Writing for ITB Postgraduate Program Ahmad Dahlan Lamongan - Mas’adah; Rina Sulistyowati; Rita Nataliawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of holding the Mendeley software training program is to make it easier for postgraduate students to write automatic bibliography as well as find references for reputable international journals and accredited national journals in particular and write citations. The method used in training activities is carried out by the team in the form of lectures, practice and question and answer. This training was conducted at the ITB Ahmad Dahlan Lamongan campus on Saturday 17 December 2022, involving lecturers from ITB Ahmad Dahlan Lamongan. The result of the training is to increase students' knowledge of using delay software and making bibliography using reference management. The implication of the training activities is that these activities can be scheduled for each batch of postgraduate students in the future